Odpowiedź :
(3x-1)/(4 )+2 ≤ (x+2)/(3 )-x mnozymy obustronnie przez 12
3(3x-1)+2 •12≤4(x+2)-12x
9x-3+24≤4x+8-12x
9x-4x+12x≤8+3-24
17x≤-13 dzielimy przez 17
x≤ -13/17
x∈(-∞, -13/17)
3(3x-1)+2 •12≤4(x+2)-12x
9x-3+24≤4x+8-12x
9x-4x+12x≤8+3-24
17x≤-13 dzielimy przez 17
x≤ -13/17
x∈(-∞, -13/17)
(3x-1)/(4 )+2 ≤ (x+2)/(3 )-x /*12
3(3x-1)+24≤4(x+2)-12x
9x-3+24≤4x+8-12x
9x-4x+12x≤8+3-24
17x≤-13
x≤-13/17
x∈(-∞, -13/17)
3(3x-1)+24≤4(x+2)-12x
9x-3+24≤4x+8-12x
9x-4x+12x≤8+3-24
17x≤-13
x≤-13/17
x∈(-∞, -13/17)
(3x-1)/(4 )+2 ≤ (x+2)/(3 )-x /*12 (mnożysz przez 12)
3(3x-1)+24≤4(x+2)-12x
9x-3+24≤4x+8-12x
9x-4x+12x≤8+3-24
17x≤-13
x≤-13/17
x∈(-∞, -13/17)
3(3x-1)+24≤4(x+2)-12x
9x-3+24≤4x+8-12x
9x-4x+12x≤8+3-24
17x≤-13
x≤-13/17
x∈(-∞, -13/17)